Implementasi Tanda Tangan Digital pada Pembuatan Surat Keterangan dengan Metodologi Scrum - Fikri Fahru Roji; Ridwan Setiawan; Ridian Gusdiana; Moch. Rizky Cahyadiputra; Wildan Hidayatul Hamdi (Institut Teknologi Garut, 2023)
In the current era of information technology, digital signatures are used as a mathematical method to identify a person or document electronically. This digital signature provides proof that the document was sent by an identified sender, and ensures the authenticity and validity of the information. The application of digital signatures, including in tertiary institutions such as the Faculty of Economics, University of Garut, can increase efficiency and change the way administrative services are carried out. Document authenticity can be verified online through a verification system that validates information. Thus, the use of digital signatures is expected to ensure document authenticity while increasing work effectiveness. This research uses the Scrum methodology, one of the Agile methodologies in product development. Scrum consists of sprint milestones that are done in no more than a month without breaks and are time-boxed. This methodology ensures an understanding of time limits and work cycles. The research stages consist of A1 Initiate, A2 Planning and Estimating, A3 Implementing, A4 Retrospect and Reviewing, and A5 Releasing. These stages are well organized to arrive at findings that are supported by scientific analysis on a regular basis. Activities in these stages include defining the project vision, building the Scrum team, user stories, sprint backlog, evaluating the sprint backlog, weekly meetings, updating the sprint backlog, reviewing and validating previous sprints, technical documentation, and application system submission. The survey results show that the Scrum methodology ranks third in the survey results with 20.3% of respondents using the Scrum methodology in the software development process.